2020
DOI: 10.3892/ijmm.2020.4796
|View full text |Cite
|
Sign up to set email alerts
|

SphK1 promotes development of non‑small cell lung cancer through activation of STAT3

Abstract: Sphingosine kinase1 (SphK1) is an oncogenic enzyme that regulates tumor cell apoptosis, proliferation and survival. SphK1 has been reported to promote the development of non-small cell lung cancer (NScLc), although the underlying mechanism remains to be determined. The aim of the present study was to examine the expression and function of SphK1 in NScLc and to explore the underlying molecular mechanism. The results of the present study demonstrated that SphK1 expression was upregulated in NScLc tissues and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…Notably, SphK1 promotes NSCLC development. Overexpression of SphK1 exacerbates the development of NSCLC by activating STAT3 [ 21 , 42–48 ]. Herein, LINC00960 sponged miR-124a to upregulate the expression of SphK1.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, SphK1 promotes NSCLC development. Overexpression of SphK1 exacerbates the development of NSCLC by activating STAT3 [ 21 , 42–48 ]. Herein, LINC00960 sponged miR-124a to upregulate the expression of SphK1.…”
Section: Discussionmentioning
confidence: 99%
“…SphK1 is therefore a potential oncotarget of NSCLC ( 38 , 39 ). Ma et al reported that SphK1 mediated signal transducer and activator of transcription 3 (STAT3) while promoting NSCLC cell proliferation and migration ( 47 ). In addition, Ni et al, showed that SphK1 is important for epithelial mesenchymal transition (EMT) in A549 cells ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer-bearing mice, targeted inhibition of SPHK1 signaling could reduce obesityrelated in ammation, S1P signal transduction, and lung metastasis and prolong survival. Additionally, several studies have shown that SPHK1 catalyzes the formation of S1P and promotes tumor cell proliferation, migration, invasion, and EMT [33]. ST3GAL4 encodes for β-galactosidase-α 2,3sialyltransferase 4, showing involvement in the biosynthesis of tumor antigens sulfo-sLe (x) and sLe (x).…”
Section: Discussionmentioning
confidence: 99%